Does Financial Synergy Provide a Rationale for Conglomerate Mergers?. (19th August 2015) - Mooney, Tim; Shim, Hyeongsop
Abstract We examine two sources of financial synergies — coinsurance effects and asset liquidity — in mergers and test whether financial synergy is greater in conglomerate mergers than horizontal mergers. We find that a reduction in cash flow volatility for consolidated firms helps enhance shareholder value. Consistent with theoretical predictions of earlier studies, our results indicate that a merger can increase shareholder value when the cash flow volatility of the consolidated firm is less than the current cash flow volatility of the acquiring firm. We present new evidence that the source of financial synergies in conglomerate mergers comes mainly from higher asset liquidity. Our test results also suggest that liquidation values are higher in conglomerate mergers than horizontal mergers holding the coinsurance effect constant, particularly when the target is financially constrained.